Pola Sebaran Permukiman Terdampak Lumpur Lapindo Sidoarjo - Moch Shofwan; Rahmatullah Agustina (COMPACT: Spatial Development Journal, 2023)
The Lapindo mud disaster is a hot mudflow event that has occurred since May 29, 2006, which caused various problems such as flooding of residential areas, agriculture, changes in population settlement patterns, limited housing supply, and migration. This study aims to determine the distribution pattern of population settlements affected by the Lapindo mudflow by taking study areas in 16 villages/kelurahan affected by the Lapindo mudflow including Besuki Village, Gempolsari Village, Glagaharum Village, Kalisampurno Village, Kalitengah Village, Keboguyang Village, Kedungbendo Village, Kedungcangkring Village, Gedang Village, Jatirejo Village, Mindi Village, Porong Village, Siring Village, Ketapang Village, Pejarakan Village, and Renokenonggo Village. By knowing the pattern of settlements, it is hoped that it will help in the process of equitable distribution of residential area development by stakeholders. With the results of the analysis of the distribution pattern, the research method used is the quantitative method using the Nearest Neighbor Analysis analysis technique using ArcMap 10.4 software. then the final result of this research will know the distribution pattern of population settlements affected by the Lapindo mudflow. The results of this study indicate that the pattern of settlements affected by the Lapindo mudflow consists of 2 (two) settlement patterns, namely clustered and random with varying NNR index values. Settlement patterns are dominated by clustered settlement patterns, namely Besuki Village, Gempolsari Village, Glagaharum Village, Keboguyang Village, Kedungcangkring Village, Gedang Village, Mindi Village, Porong Village, Ketapang with the highest NNR value in the clustered settlement pattern, namely Gedang Village. of 0.68 and the lowest NNR value is in Besuki Village of 0.25 while for random settlement patterns it is found in Kalitengah Village with an NNR value of 0.87 and Keboguyang Village with an NNR value of 0.80.